2011
DOI: 10.1021/jf103808t
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Veterinary Drugs and Metabolites in Milk Using Quadrupole Time-of-Flight Liquid Chromatography−Mass Spectrometry

Abstract: A quadrupole time-of-flight (Q-TOF) liquid chromatography-mass spectrometry (LC-MS) method was developed to analyze veterinary drug residues in milk. Milk samples were extracted with acetonitrile. A molecular weight cutoff filter was the only cleanup step in the procedure. Initially, a set of target compounds (including representative sulfonamides, tetracyclines, β-lactams, and macrolides) was used for validation. Screening of residues was accomplished by collecting TOF (MS(1)) data and comparing the accurate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
39
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(42 citation statements)
references
References 39 publications
2
39
0
1
Order By: Relevance
“…Subsequently, a standard was purchased, and it was determined that the retention time and product ions also matched that compound. The metabolite desethylene-enrofloxacin (des-ENRO) that had been found earlier in milk samples from cows dosed with ENRO 33 was also found in the catfish dosed with this drug. Thiabendazole was also identified in one regulatory eel sample when the data were compared to the larger veterinary drug database, although the estimated levels were quite low (<1 μ g/kg when compared to a solvent standard).…”
Section: Resultsmentioning
confidence: 75%
“…Subsequently, a standard was purchased, and it was determined that the retention time and product ions also matched that compound. The metabolite desethylene-enrofloxacin (des-ENRO) that had been found earlier in milk samples from cows dosed with ENRO 33 was also found in the catfish dosed with this drug. Thiabendazole was also identified in one regulatory eel sample when the data were compared to the larger veterinary drug database, although the estimated levels were quite low (<1 μ g/kg when compared to a solvent standard).…”
Section: Resultsmentioning
confidence: 75%
“…That value meets the residue limit of SNs in pork according to EU Council Regulation 470/2009/EC (Council Regulation (EEC) ()) and the U.S. Food and Drug Administration in CFR Title 21 (United States Food & Drug Administration, ). Hence, Q‐TOF/MS is capable of performing high‐throughput screening for daily monitoring of those compounds with higher residue limits (Turnipseed, Storey, Clark, & Miller, ).…”
Section: Resultsmentioning
confidence: 99%
“…The NRCP is an attribution of Ministry of Agriculture, Livestock and Food Supply (MAPA) [9,10]. Many studies have reported methodologies based on liquid chromatography couple to mass spectrometry in single or tandem mode (LC-MS and LC-MS/MS, respectively) to determine macrolides and lincosamides residues in milk [11][12][13][14] and muscle [15][16][17][18][19][20][21], and also in different matrices, such as honey [22,23], eggs [24], fish [25] and kidney [26,27]. These compounds are routinely included in multiresidue methodologies [14,16,19,[22][23][24][28][29][30][31], and there is minor publications of macrolides class only [32,33] or macrolides and lincosamides only [21].…”
Section: Introductionmentioning
confidence: 99%